PENGARUH PENERAPAN STRATEGI KOMUNIKASI PEMASARAN TERPADU PADA PRODUK EKONOMI KREATIF TERHADAP DAYA TARIK KOTA CIMAHI SEBAGAI DESTINASI PARIWISATA - Edwin Adriansyah (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
The purpose of the research is to identify and analyze (1) the implementation of integrated marketing communication strategy toward creative economy product (2) the assessmen of the attractiveness of Cimahi as a photography tourism, (3) the of influence the implementation of integrated marketing communication strategy on Cimahi become an attraction as a tourist destination. Based on the results of the research indicates that (1) the majority of respondents agree with the existence of integrated marketing communication strategy. That is the overall manager of tourism and creative economy of the tourism industry has conducted a series of promotions to introduce what all prospective travelers have through various media, (2) the majority of respondents agree with the existence of a tourist attraction. This means that tourists who consider the offered tourism positively, are not separated from the role of various parties that facilitate and support the development of tourism sector, especially in creative industry Cimahi, (3) Based on the analysis, it can be seen that the probability significance or p value is 0.000 or less than 0.05 or 5% and positive regression coefficient 0.657, which means integrated marketing communications strategy and significant positive effect with 42.1%. Based on this calculation it can be concluded that the feasibility of the influence of integrated marketing communication strategy creative economy products received and executed properly. An integrated marketing communications strategy creates a positive impact on the attractiveness of tourism attraction.